Molecular Basis for the Recognition of Herpes Simplex Virus Type 1 Infection by Human Natural Killer Cells - Dai, Hong-Sheng; Caligiuri, Michael A. (Frontiers in Immunology, 2018)
Primary infection with Herpes Simplex Virus Type 1 (HSV1) is subclinical or only mildly symptomatic in normal individuals, yet the reason for the body’s effective immune defense against this pathogen prior to antigen-specific immunity has not been well understood. It is clear that human natural killer (NK) cells recognize and kill HSV1-infected cells, and that individuals who either lack or have functionally impaired NK cells can suffer severe, recurrent, and sometimes fatal HSV1 infection. In this article, we review what is known about the recognition of HSV1 by NK cells, and describe a novel mechanism of innate immune surveillance against certain viral pathogens by NK cells called Fc Bridged Cell-mediated Cytotoxicity.